Watchdog of Natural Resources Transparency? : Evaluating Print Media Oversight of Tanzania’s Extractive Industry - Katunzi, Abdallah; Ndati, Ndeti; Thuo , Jane (University of Dar es Salaam Library Journal, 2026)
This study examines the role of newspapers as watchdogs in overseeing Tanzania’s extractive industry, a sector vital to the country’s economy yet fraught with governance and transparency challenges, through vital information dissemination intervention. The study utilises an exploratory mixed-methods approach. Its quantitative content analysis covers information carried in five leading national newspapers—Mwananchi, The Citizen, Nipashe, The Guardian, and Daily News—published in 2009, 2014, and 2019. This analysis evaluates the coverage of extractive industry transparency in accordance with the 2023 Extractive Industries Transparency Initiative (EITI) standards. Subsequently, the research engages key respondents to gain deeper insights into the quantitative findings. The findings reveal that of 720 newspaper editions, only 52 media units were relevant, as they provided information on extractive industry transparency. In total, only 52 media articles contained the required information over more than 1,000 days. The newspapers’ coverage of the extractive industry contracts, Production Sharing Agreements (PSAs) and Mineral Development Agreements (MDAs) is almost non-existent, with only one article covering the leaked Statoil addendum. Beneficial ownership, a critical aspect in revenue transparency, received zero coverage, indicating a lack of interest in the topic. Information on the extractive industry revenue has been more prominently covered than other aspects of the EI transparency. The coverage focuses primarily on the amount of revenue the government loses. The media highlights the need for the government to increase revenue from extractive industries by providing salient information on the causes of revenue losses, including smuggling, tax evasion through over-invoicing, and unfavourable contract terms. The article recommends establishing a firm editorial policy that prioritises coverage of the extractive industry. Journalists need specialised training to navigate the complexities of the extractive sector and attendant issues of disseminating such information. News media should also actively collaborate with CSOs and other stakeholders who advocate for transparency and accountability in the extractive industry.